Concentrações séricas e peritoneal de proteínas de fase aguda em equinos submetidos à endotoxemia experimental, tratados ou não com lidocaína - Yanaka, Rodrigo [UNESP] (2013)
Endotoxins are often found in high concentration in the peritoneal fluid from horses with acute gastrointestinal disease and blood of septicemic foals. The conditions mentioned earlier can lead to inflammatory processes and cause changes in the concentrations of acute phase proteins. The objectives of this study were to determine by means of polyacrylamide gel electrophoresis (SDS-PAGE), the concentrations of acute phase proteins (transferrin, ceruloplasmin, albumin, haptoglobin and acid glycoprotein) in serum and peritoneal fluid of horses submitted to experimental endotoxemia and evaluate the possible effects of the administration of lidocaine on the production of these proteins after intraperitoneal injection of endotoxin in these animals. To this end, 12 animals were distributed in two groups, control which was treated with 0.9% NaCl solution and the experimental which was treated with continuous infusion for 6 hours of 2% lidocaine solution. It is concluded that in this experimental model the intraperitoneal administration of endotoxin caused an increase in the concentrations of peritoneal transferrin, ceruloplasmin and haptoglobin in the control group, of albumin in both groups, and the acid glycoprotein in the group treated with infusion of lidocaine. However, the absence of changes in the concentrations of serum ceruloplasmin, serum albumin, haptoglobin and acidic glycoprotein indicate that the amount of the circulatory endotoxin was not enough to alter serum concentrations of these proteins. The continuous infusion of lidocaine interfered in peritoneal acute phase proteins values and had an anti-endotoxemic effect